Isolation and characterization of the oil bodies and oleosin of coconut(Cocos nucifera l.) - Rodelas, Abigail Joy D.; Regalado, Ellen S.; Bela-ong, Dennis B.; Garcia, Roberta N.; Laurena, Antonio C.; Tecson-Mendoza, Evelyn Mae (2008)
Oil bodies were isolated from the solid endosperm of 11-12 month old coconut and purified by sucrosedensity gradient washing, urea washing and floatation centrifugation. Under light microscope, purifiedoil bodies showed two types of small and large oil bodies: about 90% with diameter of 0.5-4.0 μm and10%, 10-40 μm, respectively. The oil bodies consisted of 97% triacylglycerols, phospholipids(phosphatidylethanoloamine and phosphatidylcholine) and the oil body storage protein oleosin. Puri-fied oleosin showed one band of 14400 on SDS-PAGE. Two-dimensional electrophoresis resolved oneband of 14400 with an isoelectric pH between 9 and 10. The 14400 band had an N-terminal amino acidsequence of GEERR or GEEER. Additional urea washings of the coconut oil bodies followed by etherdelipidation revealed two oleosin bands of 14400 and 11000 Mr on SDS-PAGE. © Published by the College of Agriculture.
Keywords: Coconut; Proteins